Relationship Between Nurses' Workload and Surgical Safety Checklist Implementation at Nahdlatul Ulama Islamic Hospital Demak - Munir, Abdul; Rajin, M; Safi'i, Akhmad; Azizah, Ninik (Al-Hijrah Indonesia, 2025)
The Surgical Safety Checklist (SSC) is an essential tool for enhancing patient safety in the operating room; however, its implementation can be influenced by nurses’ workload, particularly in the Central Surgical Installation (IBS) at Nahdlatul Ulama Islamic Hospital (RSI NU) Demak. This study employed a quantitative cross-sectional design involving 15 nurses, with data collected through a workload questionnaire and SSC implementation observations, followed by univariate and bivariate analysis using Spearman’s correlation. Results showed that the majority of nurses experienced a light workload (67%), with a smaller proportion in the moderate category and very few in the heavy category, possibly influenced by long work experience (>20 years) causing some nurses to perceive routine tasks as light. Most SSC implementations were classified as good (60%), with a smaller number rated as fairly good, and very few rated as poor. Bivariate analysis indicated a significant positive correlation between nurses’ workload and SSC implementation (rs = 0.549, p = 0.034). These findings suggest that even among nurses with higher workloads, SSC implementation remains good, likely influenced by extensive work experience, professional motivation, and a strong safety culture in the IBS. Nurses with lower SSC performance may benefit from targeted refresher training or additional supervision to ensure the quality and safety of surgical care is maintained.